Ethical dilemmas concerning orthodontic treatment among orthodontists in a sample from Saudi Arabia: a pilot study - Nawaf H. Al Shammary; Abdulrahman K. Alshammari (BMC Medical Ethics)
Abstract Background Ethics is based on moral principles that should be the foundation for every healthcare decision, however, ethical concepts can often be challenging to define in specific clinical scenarios. There are several instances where a practising clinician often finds it difficult to make a proper decision despite maintaining integrity and professionalism. The objective of the present study was to explore the ethical dilemma faced by orthodontists practicing in Saudi Arabia concerning orthodontic treatment. Method This was a questionnaire-based cross-sectional study that was adapted from the scenarios of ethical dilemmas presented by Jerrold in 1998. Ten orthodontists from each province of Saudi Arabia were requested to participate in this study and the questionnaire were sent through email and their responses were analysed. Results A total of 37 responses were obtained (out of 130) with a response rate of 28.46%. Among them 23 were female and 14 were male. Most participants belonged to the age group 30–39 years and most of them have clinical experience of more than 5 years. There was a wide variation in the responses among the participants in all the scenarios presented. The median likelihood of getting similar scenarios in their clinical practice in Saudi Arabia ranged from 3 to 3.5. Conclusion There was a wide variation in the opinion among the practising orthodontists in Saudi Arabia in the scenarios presented. The presented scenarios are less likely to be perceived in the local context and some new situations of ethical dilemmas are identified.